(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: To determine the etiologic factors responsible for primary amenorrhoea on the basis of clinical examination and laboratory investigations. Materials & Methods: This retrospective study was done in a private setting from the records of the patients between January 2005 - December 2007. Results: During three years of study period, 44 cases of primary amenorrhoea were analyzed. Two most common etiologic factors were mullerian agenesis (36.3%) and gonadal dysgenesis (29.5%). Range of average age of the patients when they first consulted the physician was 13- 32 years. Karyotyping was done on 10 of13 cases of gonadal dysgenesis; 46, XX karyotype was found in 50% and 45, XO in 10% of analyzed cases. Clinical examination gave wrong diagnosis of absent uterus in two cases who were in the hypoestrogenic stage with hypoplastic uterus; ultrasonography gave the wrong diagnosis in one case in this study. These patients successfully menstruated after hormone replacement therapy. Conclusion: The etiologic causes and cytogenetic study of primary amenorrhoea in our study is different from earlier reports. Racial and environmental differences may play a role in these differences. The facilities for diagnostic tools may also play a part. Both clinical examinations and many laboratory investigations have to be completed before final diagnosis of etiologic causes of primary amenorrhoea are elucidated. Diagnosis based on inadequate data can be misleading. DOI: 10.3329/bjog.v23i2.4958 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 46-50